The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1099/jmm.0.46105-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of visible light on malodour production by mixed oral microflora

Abstract: Oral malodour is considered to be caused by the proteolytic activity of anaerobic Gram-negative oral bacteria. In a previous study, it was shown that these bacteria were susceptible to blue light (wavelengths of 400-500 nm). In this study, the effect of blue light on malodour production by mixed oral microflora was tested in a salivary incubation assay. Whole saliva samples were exposed to a xenon light source for 30, 60, 120 and 240 s, equivalent to fluences of 34, 68, 137 and 274 J cm À2 , respectively. Malo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
(23 reference statements)
2
15
0
Order By: Relevance
“…photodynamic treatment) has been reported in the literature (Wilson, 1994;Henry et al, 1995Henry et al, , 1996Konig et al, 2000;Soukos et al, 2005), and it has been suggested that this effect is mediated through the production of ROS (Gourmelon et al, 1994). This hypothesis is further supported by the observation that obligate anaerobic oral bacteria (pigmented and non-pigmented) are more susceptible to blue light exposure treatment than facultative ones (Feuerstein et al, 2004;Sterer & Feuerstein, 2005). Various studies have reported that using the colourant erythrosine B as a photosensitizer enhances the antimicrobial properties of blue light from light-emitting diode (LED) or halogen light sources (De Lucca et al, 2012;Lee et al, 2012).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…photodynamic treatment) has been reported in the literature (Wilson, 1994;Henry et al, 1995Henry et al, , 1996Konig et al, 2000;Soukos et al, 2005), and it has been suggested that this effect is mediated through the production of ROS (Gourmelon et al, 1994). This hypothesis is further supported by the observation that obligate anaerobic oral bacteria (pigmented and non-pigmented) are more susceptible to blue light exposure treatment than facultative ones (Feuerstein et al, 2004;Sterer & Feuerstein, 2005). Various studies have reported that using the colourant erythrosine B as a photosensitizer enhances the antimicrobial properties of blue light from light-emitting diode (LED) or halogen light sources (De Lucca et al, 2012;Lee et al, 2012).…”
Section: Discussionsupporting
confidence: 53%
“…A previous study has demonstrated that exposing mixed planktonic bacteria from saliva to non-coherent blue light results in reduced malodour production in a salivary incubation assay (Sterer & Feuerstein, 2005). In the present study, an experimental biofilm system was utilized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the saliva-putrefaction system has shown that green tea, mints and toothpaste exhibited encouraging values that dispose one to accept these products as efficient VSC inhibitors. A saliva-putrefaction system has been employed in other studies to determine the efficacy of products in reducing oral malodor (23)(24)(25). However, when a treatment is carried out on saliva itself, as in this study, in vitro results do not always conform to in vivo results.…”
Section: Discussionmentioning
confidence: 99%
“…Halimeters ® are now mostly used in dental clinics [122][123][124][125]. However, a Halimeter does not identify the composition of sulfur compounds.…”
Section: Halitosismentioning
confidence: 99%